Development of enzyme-linked immunosorbent test for the detection of tick-borne encephalitis virus-specific antibody responses - Jartti, Anna (My University, 2025)
Tick-borne encephalitis virus (TBEV) infection can lead to a severe disease called tick-borne encephalitis (TBE). Diagnosis is established by measuring TBEV specific IgM antibodies usually from blood serum using enzyme-linked immunosorbent assays (ELISA). Effective vaccines against TBEV are available in Europe. In rare cases a TBEV-infection can lead to a disease also in vaccinated individuals. This is called vaccination breakthrough (VBT) infection. The vaccines contain only structural TBEV proteins, and antibodies against nonstructural proteins (e.g. NS1) form only after TBEV infection. Therefore, vaccinees, infected individuals and VBTs can in principle be separated by their antibody response. In this project, TBEV envelope (E) and non-structural (NS1) proteins were produced as glutathione S-transferase (GST) fusion proteins in insect cells (Sf-9). Protein production in Sf-9 cells was confirmed with western blot. Protein purification was performed using GST affinity column. The E protein was additionally produced in mammalian HEK293 cells with His-tag and purified with nickel-nitrilotriacetic (Ni-NTA) column. The purified proteins were utilized to set up the ELISA test using a panel of serum samples from TBEV infected and vaccinated individuals. Detection of E and NS1 specific antibodies was tested also using immunoblot strip assay. E and NS1 proteins were expressed well in insect cells, however, the purification of NS1 was unsuccessful. The use of E proteins produced in insect cells (E-GST) and HEK293 cells (E-His) as antigens in ELISA was analyzed. The IgG ELISA parameters were successfully optimized with E-His protein, but IgM antibody levels were constantly low. In immunoblot strip assay, one infected serum sample contained antibodies that recognized the linearized E-GST protein. In this study, a TBEV E-protein specific IgG ELISA test was developed. In the future, E-His ELISA test will be optimized for IgM antibody measurement. Because NS1 protein is important in separating the infected and vaccinated individuals, the challenges in NS1 protein production need to be resolved.
Keywords: tick-borne encephalitis virus, ELISA, serology, vaccine